2007
DOI: 10.1016/j.pep.2006.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of recombinant human stefin A in mammalian and bacterial cells

Abstract: Recombinant human cysteine protease inhibitor, stefin A, was expressed in both E. coli and BSC-1 monkey kidney cells utilizing pET and recombinant Vaccinia virus systems, respectively. The expressed protein was purified and analyzed by SDS-PAGE and western blot analysis utilizing a polyclonal antibody against rat cystatin α. In both cases the purified protein appeared as a single band corresponding to the molecular weight of stefin A (~10 kDa). Viability of the expressed stefin A was determined by the inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The K i values are to be seen as approximate because corrections for substrate‐induced dissociation of enzyme–inhibitor complexes and formation of oligomeric states of stefins were not made . The K i value obtained was about six times higher than the value obtained using the E. coli expressed recombinant HSA and closely resembled the value obtained from the mutational study of E. coli expressed recombinant HSB . As previously reported, the differences in the value should not be overstressed because of the experimental difficulties of K i determination .…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…The K i values are to be seen as approximate because corrections for substrate‐induced dissociation of enzyme–inhibitor complexes and formation of oligomeric states of stefins were not made . The K i value obtained was about six times higher than the value obtained using the E. coli expressed recombinant HSA and closely resembled the value obtained from the mutational study of E. coli expressed recombinant HSB . As previously reported, the differences in the value should not be overstressed because of the experimental difficulties of K i determination .…”
Section: Resultssupporting
confidence: 47%
“…In the present study, we found that HSA and HSB exhibited different molecular stabilities during a 6‐day incubation at 37°C under neutral pH conditions, with HSB showing more vulnerability to fibril formation even under mild incubation conditions. Although the expression of functional recombinant HSA and HSB in E. coli has been previously reported , the proteins were contained N‐/C‐terminal extensions and/or were fused with tags. In addition, as recombinant HSA and HSB are often expressed as inclusion bodies in E. coli , an additional solubilizing process may be required for their purification.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggest that CSTA plays a critical role in the proliferation and differentiation of keratinocytes, and in regulating antigen presentation and apoptosis [ 66 - 68 ]. Importantly, down-regulation of CSTA has been detected in a wide range of epithelial tumors [ 69 ], which further indicates its important role in the differentiation and development of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%